Analisis Nilai-Nilai Zuhud dalam Kitab Irsyadul ‘Ibad Karya Zainuddin Ibnu Abdul Aziz Al-Malybari - Muhammad Riki; Abu Mansyur; Rohmadi Rohmadi (Indonesian Journal of Behavioral Studies, 2021)
The zuhud values ​​in the book Irsyadul 'Ibad that will be discussed by this researcher are moral values. These zuhud values ​​will lead us to the true zuhud, because they teach us how to be obedient and have faith in Allah SWT by carrying out all orders and leaving all His prohibitions and behaving or having good character. Thus we will understand the nature of the world and the hereafter. Then there will be motivation / encouragement from within us to prioritize the hereafter rather than the world just to get the pleasure of Allah SWT. May Allah SWT instill in our hearts the zuhud nature and make us as people who prioritize the hereafter over the world. The type of research used is library research. The research technique used is documentation. The data analysis technique used is content analysis, namely identifying, describing, analyzing, and compiling descriptive explanations of the content of zuhud values ​​in the book of Irsyadul 'Ibad. The results of the study are zuhud values ​​in the book of Irsyadul 'Ibad, namely sincerity, care, patience, tawadhu, courage and hard work. Morals have a very important role in human life to form characters and souls that believe and fear Allah SWT, study and practice religious teachings in the life of the nation and state. Therefore, moral values ​​must be instilled in humans from an early age.